2003
DOI: 10.1063/1.1624059
|View full text |Cite
|
Sign up to set email alerts
|

Quantum and tensorial modeling of multipolar nonlinear optical chromophores by a generalized equivalent internal potential

Abstract: Articles you may be interested inStudy of linear and nonlinear optical properties of dendrimers using density matrix renormalization group method J. Chem. Phys. 131, 074111 (2009); 10.1063/1.3202437 Quantum-chemical investigation of second-order nonlinear optical chromophores: Comparison of strong nitrilebased acceptor end groups and role of auxiliary donors and acceptorsThe equivalent internal field model, originally developed for linear one-dimensional chromophores, is extended to three-dimensional multipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…[37]. Although this model is not valid for 2-or 3-dimensional charge transfer processes [38], it has been shown that in the case of purely octupolar systems, the 3-level dispersion equation is equivalent to the 2-level one owing to the degeneracy of the two excited states [39]. In the case of MLCT additional transition for copper complexes, the weak molar absorption coefficient associated to it makes its contribution to the b values almost negligible.…”
Section: Measurementsmentioning
confidence: 96%
“…[37]. Although this model is not valid for 2-or 3-dimensional charge transfer processes [38], it has been shown that in the case of purely octupolar systems, the 3-level dispersion equation is equivalent to the 2-level one owing to the degeneracy of the two excited states [39]. In the case of MLCT additional transition for copper complexes, the weak molar absorption coefficient associated to it makes its contribution to the b values almost negligible.…”
Section: Measurementsmentioning
confidence: 96%
“…Zyss has widely demonstrated the interest of multipolar systems for quadratic NLO [107][108][109]; on the basis of his theory, efficient octupolar quadratic nonlinear systems have been designed [110][111][112][113][114][115][116]. This symmetry has been considered as a new strategy for the design of efficient systems in the field of TPA.…”
Section: Branched Moleculesmentioning
confidence: 99%
“…The corresponding static hyperpolarizability values b HRS (0) were also derived. 4,16,17 Among the organic compounds 1-X and 2-X, increasing the donating strength of the substituents or the length of the bridge results in an enhancement of b HRS , which is partly attributable to dispersion factors, according to the corresponding b HRS (0) values. The electronic effect of the X substituent on b HRS (0) values appears predominant over the bridge elongation.…”
mentioning
confidence: 99%